CORRELATION OF COMMUNITY PHARMACIST KNOWLEDGE, ATTITUDES, AND PRACTICES IN THE DETECTION OF TUBERCULOSIS CASES IN WEST JAVA PROVINCE - Mardhiyyah, Cut Ainul; Zuniarto, Ahmad Azrul; Amanatin, Alfitia Dwi; Ryansyah, Hardi; Antonia, Vonny (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Tuberculosis (TB) control is hampered by suboptimal case detection and treatment delays. Pharmacies are reported as a first-aid treatment for patients with TB. Therefore, researchers analyzed knowledge, attitudes, and practices (KAP) regarding TB case detection among community pharmacists, aiming to find innovative strategies to involve community pharmacists in TB case detection. The research aims to determine the level of knowledge, attitudes, and practices, and the relationship between knowledge and attitude, knowledge-practice, and attitude-practice of community pharmacists in detecting tuberculosis cases in West Java Province. This research uses a descriptive observational method with 419 pharmacists who practice pharmacies. The results showed that pharmacists had a sufficient level of knowledge (14.94 ± 1.99), an adequate level of attitude (63.58 ± 9.12), and a sufficient level of practice (20.58 ± 8.55) regarding TB case detection. There is a very low relationship between knowledge and attitude (p-value 0.024<0.05), knowledge and practice ( p-value 0.018>0.05), and attitude and practice ( p-value 0.000< 0.05). This study concluded that community pharmacists in West Java Province have sufficient knowledge, attitudes, and practices in detecting TB cases, but the level of relationship between knowledge attitude and detecting TB cases, and the level of association between knowledge attitude and knowledge practice was very low, while the relationship between attitude practice was low. Keywords: Pharmacist, Knowledge, Practice, Attitude, Tuberculosis